المصحف الشريف - Library of the Holy Quran | مكتبة المصحف الشريف (2023)
Securitization 307 leaves, 15 lines, 17 x 11 cm. Bright font type. The resource type is Text. The beginning of the manuscript: In the name of God, the Most Gracious, the Most Merciful. The end of the manuscript. Say, I seek refuge in the Lord of the people, the King of the people, the God of the people... God Almighty has spoken the truth, and His Holy Messenger reached the year one hundred and forty-six. The form is an image. Member of the Holy Quran Library. | التوريق 307 ورقة، 15 سطر، 17×11سم. نوع الخط مشرقي. نوع المورد نص. بداية المخطوط بسم الله الرحمن الرحيم، الحمد لله رب العالمين، الرحمن الرحيم... نهاية المخطوط قل أعوذ برب الناس، ملك الناس، إله الناس... صدق الله العظيم، وبلغ رسوله الكريم، سنة مائة وألف أربعون ستة. النموذج صورة. عضو في مكتبة المصحف الشريف.